(untitled) (Physical Education, Health and Social Sciences, 2025)
The role of emotional intelligence in sports coaching has gained increasing attention as coaching practices evolve beyond technical instruction to encompass psychological, emotional, and social dimensions. This study investigates the impact of emotional intelligence on coaching effectiveness, athlete motivation, and team cohesion. Employing a quantitative descriptive and correlational research design, data were collected from 100 sports coaches across multiple disciplines using a structured questionnaire and analyzed through SPSS. Results indicate a strong positive correlation between emotional intelligence and coaching effectiveness (r = .786, p < .01), with emotional intelligence explaining 61.7% of the variance in coaching outcomes (R² = .617). Coaches with higher emotional intelligence demonstrated greater self-awareness, emotional regulation, empathy, and interpersonal skills, which positively influenced decision-making, stress management, and coach-athlete relationships. The findings underscore the importance of integrating emotional intelligence development into coach education programs and professional training, suggesting that emotionally intelligent coaches foster enhanced team cohesion, improved athlete performance, and more effective leadership. This study contributes to the literature by highlighting emotional intelligence as a critical factor in optimizing sports coaching outcomes and offers practical implications for training, policy, and future research in sports contexts.